The Rational Emotive Behavior Counseling Model to Develop Positive Conformity of the Learners - Suhendri Suhendri; Dwi Yuwono Puji Sugiharto; Mungin Eddy Wibowo; Mulawarman Mulawarman (Universitas Negeri Semarang, 2022)
Abstrak. The incapability to manage emotion and feeling makes learners triggered to commit inappropriate conformity feelings. Rational emotive behavior counseling becomes an intervention model to relieve anxiety and to help the counseling process in measuring feelings and emotions. This research determined the contribution of the rational emotive counseling behavior model to developing learners' positive conformity. This ex post facto research applied true experimental design. The research subjects consisted of 20 learners. Then, the researchers grouped them into two groups. They were an experimental group with 10 learners and a control group with the other 10 learners. The applied data collecting techniques were measured through interviews and a positive conformity instrument consisting of 32 items. The obtained coefficient of Cronbach Alpha was 0.802. The data analysis applied inferential analysis with the t-test formula. The rational emotive behavior counseling model significantly influenced the experimental group’s improvement. The applied counseling model, rational emotive behavior, was effective to improve the learners’ positive conformity. Both groups, experimental and control groups, experienced significant and different improvements. The experimental group had significantly improved positive conformity to the control group. Thus, the rational-emotive counseling model was effective to develop the positive conformity of the learners.